2023
DOI: 10.3390/medicina59081391
|View full text |Cite
|
Sign up to set email alerts
|

Training in Aortic Arch Surgery as a Blueprint for a Structured Educational Team Approach: A Review

Philipp Discher,
Maximilian Kreibich,
Tim Berger
et al.

Abstract: Background and objectives: The treatment of pathologies of the aortic arch is a complex field of cardiovascular surgery that has witnessed enormous progress recently. Such treatment is mainly performed in high-volume centres, and surgeons gain great experience in mastering potential difficulties even under emergency circumstances, thereby ensuring the effective therapy of more complex pathologies with lower complication rates. As the numbers of patients rise, so does the need for well-trained surgeons in aorti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…The printing success of such 3D models reached around 85% for standard clear resin in a study by Kaufmann et al [34]. A study by Discher et al found that the results of the surgeries were comparable whether the procedures were performed by a specialist or by a trainee who has trained in simulation-based settings, assisted by the specialist [35].…”
Section: Utilization In Trainingmentioning
confidence: 99%
“…The printing success of such 3D models reached around 85% for standard clear resin in a study by Kaufmann et al [34]. A study by Discher et al found that the results of the surgeries were comparable whether the procedures were performed by a specialist or by a trainee who has trained in simulation-based settings, assisted by the specialist [35].…”
Section: Utilization In Trainingmentioning
confidence: 99%